Do Not Offend the Flies: Не обижайте мух - Timofeeva , Oxana; Jovanchevski, Andrej (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Oxana Timofeeva | Оксана Тимофеева Title (English): Do Not Offend the Flies Title (Russian): Не обижайте мух Translated by (Russian to English): Andrej Jovanchevski | Андреј Јованчевски Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 68-72 Page Count: 5 Citation (English): Oxana Timofeeva, “Do Not Offend the Flies,” translated from the Russian by Andrej Jovanchevski, Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 68-72. Citation (Russian): Оксана Тимофеева, “Не обижайте мух,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 68-72.